Mechanical, chemical performance, and microstructural behavior of montmorillonite-burnt red soil bricks incorporating coffee ash biochar - Hepautwa, Amani Abdallah; Jande, Yusufu A. C. (Frontiers in Built Environment, 2025)
This paper investigates the application of circular economy principles by recycling spent coffee grounds (SCG) to produce coffee ash biochar (CAB), which is then used in the creation of burnt red soil bricks (BRSB) fired at temperatures between 900 °C and 1,100 °C, with 10% Montmorillonite as an additive (Al-Hasani, 2024; Cano and Reyes-Vallejo and Sánchez-Albores and Sebastian and Cruz-Salomón and d. Hernández-Cruz and et al., Sustainability, 2025, 17(1), 99; Chop, Investigation of Coal Combustion Residuals for Ceramic Applications and Production, 2024; Chung et al., Waste and Biomass Valorization, 2021, 12, 6273–6291; George, Electrical and mechanical characteristics of carbonaceous composites, 2023; Goswami and Kushwaha and Kafle and Kim, Catalysts, 2022, 12(8), 817). Comprehensive comparisons were made using coffee ash pyrolyzed at temperatures of 300 °C, 350 °C, and 500 °C, as substitutes for red soil at replacement levels of 5%, 10%, 15%, and 20%. The results indicated a decreasing trend in the mechanical properties of the burnt red soil bricks with increasing coffee ash content. Under optimal water-cement (w/c) ratios, the compressive strength (CS) of red soil bricks containing 5% SCG increased by 49.7% compared to the control when pyrolyzed at 350 °C. For bricks with 10% SCG, compressive strength improved by 53.5%, while flexural strength (FS) increased by 66.1% and splitting tensile strength (TS) rose by 38.4% when pyrolyzed at 300 °C. Additionally, the study found significant reductions in water, chloride, and sulfur penetration by 41.5%, 44.4%, and 34.3%, respectively, indicating improved durability and resistance to environmental factors. The water permeability coefficient remained relatively consistent across samples. This innovative approach addresses the disposal challenges of spent coffee grounds while benefiting both the economy and the environment. This study demonstrates the feasibility of incorporating SCG into burnt red soil bricks and examines the impact of SCG on their performance. Experimental results were analyzed through range analysis and analysis of variance to identify optimal combinations for varying performance requirements. Microstructural evaluations were performed using Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), and Differential Scanning Calorimetry (DSC) techniques (Singh and Patel, Journal of Material Cycles and Waste Management, 2025, 27(1), 170–192). These analyses provided insights into the structural integrity and bonding mechanisms within the composite materials. The findings suggest that SCG pyrolyzed at 300 °C and 350 °C, particularly at a 10% and 5% replacement level, delivers the best mechanical and chemical performance (Hanfi and Saftah and Alsufyani and Alqahtani and Mahmoud, Radiation Physics and Chemistry, 2025, 226; Mohammed and Joy and Zahid and Rafid, Journal of Materials in Civil Engineering, 2025, 37(5)). The study highlights the environmental benefits of using spent coffee grounds (SCG) in red soil brick manufacturing, reducing landfill waste and carbon emissions. This approach promotes resource efficiency and sustainable construction. Future work will focus on durability and scalability for industrial applications.